Clinical Case 29—The role of transthoracic echocardiography on patients presenting with shock of unknown etiology. (21st October 2022) - de Figueiredo, Margarida Gancho; Figueiredo, Margarida; Santos, Mariana; Santos, Hélder; Almeida, Samuel
Abstract: Seventy-six-year-old woman, with a previous medical history of arterial hypertension, dyslipidaemia, hypothyroidism and mitral valve plasty (previous rheumatic fever) presents to the emergency department with unspecific complaints of malaise, productive cough and dyspnoea for the past 15 days. At admission, the patient was conscient, apyretic, tachycardic, hypotensive and with peripheric oxygen saturation of 90% (on room air). The patient became haemodynamically unstable and unresponsive. Electrocardiogram with sinus tachycardia, SIQIII pattern and a slight ST elevation in aVR and ST depression in DI, aVL and precordial leads. TTE revealed right cavities dilatation and the presence of a serpiginous echogenic mass that protruded from the inferior vena cava crossing the right atrium and reaching the right ventricle. Thrombolysis, fluid challenge and vasopressor perfusion were immediately started with a good clinic response. Haemodynamic stability was achieved 5 hours after the thrombolysis. An unfractionated heparin perfusion was initiated after the thrombolysis and discontinued 24 h after the patient was admitted. The remaining hospitalization was uneventful and the patient was discharged 7 days after on a non-vitamin K antagonist oral anticoagulant. TTE revaluation before discharge revealed mild dilatation of the right cavities with mild systolic dysfunction of the right ventricle and a normal PSAP. There is no scientific evidence regarding the best strategy to approach a patient with a migrating thrombus and TTE is of high value in the case of shock due to its high specificity as a rule-in test, especially when the patient cannot undergo other types of exams. Figure 1 Transthoracic echocardiography (subcostal 4 chamber view) showing the presence of a serpiginous echogenic mass in the right atrium (red arrow).